Trends in the use, complications, and costs of permanent pacemakers in Australia: A nationwide study from 2008 to 2017. Issue 2 (18th January 2021) - Westaway, Samuel; Nye, Elsbeth; Gallagher, Celine; Tu, Samuel J.; Clarke, Nicholas; Hanna‐Rivero, Nicole; Emami, Mehrdad; Kadhim, Kadhim; Pitman, Bradley M.; Mahajan, Rajiv; Lau, Dennis H.; Young, Glenn D.; et al.
Abstract: Objective: To characterize contemporary pacemaker procedure trends. Methods: Nationwide analysis of pacemaker procedures and costs between 2008 and 2017 in Australia. The main outcome measures were total, age‐ and gender‐specific implant, replacement, and complication rates, and costs. Results: Pacemaker implants increased from 12, 153 to 17, 862. Implantation rates rose from 55.3 to 72.6 per 100, 000, a 2.8% annual increase (incidence rate ratio [IRR] 1.028; 95% CI, 1.02–1.04; p  < .001). Pacemaker implants in the 80+ age group were 17.37‐times higher than the < 50 group (95% CI 16.24–18.59; p  < .001), and in males were 1.48‐times higher than in females (95% CI 1.42–1.55; p  < .001). However, there were similar increases according to age ( p  = .10) and gender ( p  = .68) over the study period. Left ventricular lead rates were stable (IRR 0.995; 95% CI 0.98–1.01; p  = .53). Generator replacements decreased from 20.5 to 18.3 per 100, 000 (IRR 0.975; 95% CI 0.97–0.98; p  < .001). Although procedures for generator‐related complications were stable (IRR 0.995; 95% CI 0.98–1.01; p  = .54), those for lead‐related complications decreased (IRR 0.985; 95% CI 0.98–0.99; p  < .001). Rates for all pacemaker procedures were consistently greater in males ( p  < .001). Although annual costs of all pacemaker procedures increased from $178 million to $329 million, inflation‐adjusted costs were more stable, rising from $294 million to $329 million. Conclusions: Increasing demand for pacemaker implants is driven by the ageing population and rising rates across all ages, while replacement and complication procedure rates appeared more stable. Males have consistently greater pacemaker procedure rates than females. Our findings have significant clinical and public health implications for healthcare resource planning.